2012
DOI: 10.1155/2012/524308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BCL2 Family of Apoptosis Regulator Proteins in Acute and Chronic Leukemias

Abstract: The disturbance of apoptosis molecular signaling pathways is involved in carcinogenesis. BCL2 family of proteins is the hallmark of apoptosis regulation. In the last decade, new members of BCL2 gene family were discovered and cloned and were found to be differentially expressed in many types of cancer. BCL2 protein family, through its role in regulation of apoptotic pathways, is possibly related to cancer pathophysiology and resistance to conventional chemotherapy. It is well known that leukemias are haematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
171
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(190 citation statements)
references
References 130 publications
5
171
0
14
Order By: Relevance
“…High Bcl2 expression was reported by Venditti et al [18] in AML M0, M1 and M6, and by Campos et al [23] in AML M4 and M5 subtypes. Also, Tzifi et al [24] noted Bcl2 positivity in immature AML subtypes and similarly present study findings show significant positive correlation of Bcl2 with CD34 and CD117. Similarly, Poeta et al [5] observed low bax/bcl2 ratio associated with high CD34 and CD117 levels while, association of Bcl2 with CD34 over expression is supported by other study groups [16][17][18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…High Bcl2 expression was reported by Venditti et al [18] in AML M0, M1 and M6, and by Campos et al [23] in AML M4 and M5 subtypes. Also, Tzifi et al [24] noted Bcl2 positivity in immature AML subtypes and similarly present study findings show significant positive correlation of Bcl2 with CD34 and CD117. Similarly, Poeta et al [5] observed low bax/bcl2 ratio associated with high CD34 and CD117 levels while, association of Bcl2 with CD34 over expression is supported by other study groups [16][17][18].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, some study groups [16,21,23,24] demonstrated that increased mean fluorescence intensity and high levels of Bcl2 expression significantly lowered the complete remission rates. With respect to treatment options, in case of AML non-M3 patient group, Bcl2 positivity showed high incidence of disease relapse in adult patients treated with 7+3 protocol and pediatric patients treated with BFM93 protocol.…”
Section: Discussionmentioning
confidence: 88%
“…These related proteins share at least one of four homologous regions termed Bcl homology (BH) domains (BH1 to BH4) which control the ability of the Bcl-2 proteins to bind to each other to form homodimers and heterodimers. BH domains contribute at multiple levels to the function of these proteins in cell death and survival (Adams and Cory, 2007;Tzifi et al, 2011). About 30 members of this family have been currently identified.…”
Section: Introductionmentioning
confidence: 99%
“…About 30 members of this family have been currently identified. Based on the functional studies and the conservation of BH domains, these proteins are divided into three subgroups, pro-survival Bcl-2 like subgroup such as Bcl-2, Bcl-xL, Mcl-1, Bcl-w, A-1 subgroup which suppress cell death, and proapoptotic Bax-like subgroup such as Bax, Bak, Bok and Bik which promote cell death (Tzifi et al, 2011;Billen et al, 2008). The Bcl-2 protein, as one of the Bcl-2 family, binds to the outer surface of mitochondria and sometimes endoplasmic reticulum, and, separating pro-apoptotic members such as Bax from mitochondria, prevents apoptotic cell death (Plati et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation